The Conundrum of Greece and the Eurozone: Puzzles, Paradoxes and Contradictions - Kitromilides, Yiannis (Panoeconomicus, 2016)
This paper examines three questions regarding the controversial relationship between Greece and the eurozone during the current crisis. First, why was Greece “bailed-out” in 2010? Second, why the Greek economy collapsed despite the largest “bail-out” in global financial history? Third, was the electoral mandate of the Syriza government for ending austerity while remaining in the eurozone contradictory? There are conflicting answers to all three questions and the paper compares the answers of the so called “dominant narrative” to those provided by the “counter-narrative” of the eurozone crisis. The paper reaches the following conclusions. First, the primary motivation for the “bail-out” of Greece was the maintenance of European and global financial stability. Second, although programme implementation was less successful in Greece than in other “programme” countries the catastrophic collapse of the Greek economy had more to do with the programme itself than its implementation. Third, the meaning of democratic decision-making in the Euro-group needs re-appraisal and must go beyond seeing the Greek demand of a policy reversal in the eurozone as simply a clash of democratic mandates in a 19 member monetary union. Political unity will not only improve efficiency but also democracy and accountability in eurozone policymaking. Key words: “Bail-out”, Expansionary austerity, Fiscal consolidation, Internal devaluation, Structural reforms, Programme implementation, Democratic dialogue. JEL: B20, B25, E44, E52, F15, H30, H60.